Loss of cytoplasmic survivin expression is an independent predictor of poor prognosis in radically operated prostate cancer patients. (1st January 2020) - Büscheck, Franziska; Sulimankhil, Mariam; Melling, Nathaniel; Höflmayer, Doris; Hube‐Magg, Claudia; Simon, Ronald; Göbel, Cosima; Hinsch, Andrea; Weidemann, Sören; Izbicki, Jacob R.; Jacobsen, Frank; Mandelkow, Tim; et al.
Abstract: Survivin is an inhibitor of apoptosis. Aberrant survivin expression occurs in malignant tumors and has often been linked to unfavorable patient outcome. Here we analyzed 12 432 prostate cancers by immunohistochemistry. Survivin immunostaining was regularly expressed at high levels in normal prostate epithelium but expression was often reduced in prostate cancers. Among 9492 evaluable prostate cancers, 9% expressed survivin strongly, 19% moderately, 28% weakly, and 44% lacked it. Loss of cytoplasmic survivin was seen in advanced tumor stage, higher Gleason score, preoperative PSA levels, and Ki‐67 labeling index, and associated with earlier PSA recurrence ( P  < .0001). Survivin loss was significantly more common in cancers carrying TMPRSS2:ERG fusions (61% survivin negative) than in ERG wild‐type cancers (32% survivin negative; P  < .0001). Multivariate analysis revealed that reduced cytoplasmic survivin expression predicted poor prognosis independent from Gleason score, pT, pN, and serum PSA level. This was valid for ERG‐positive and ERG‐negative cancers. Survivin expression loss even retained its prognostic impact in 1020 PTEN deleted cancers, a group that is already characterized by dismal patient prognosis. In conclusion, reduced survivin expression is associated with more aggressive tumors and inferior prognosis in prostate cancer. Abstract : Survivin encoded by the BIRC5 gene was analyzed by immunochemistry on a tissue microarray of 12 432 prostate cancers. We found loss of survivin expression linked to early PSA recurrence in patients treated with radical prostatectomy. Loss of survivin expression showed a moderate and independent impact on PSA recurrence‐free survival. This effect remained also in PTEN‐deleted cancers.